Unnatural selection: reducing antibiotic resistance in neonatal units. Issue 1 (20th December 2005) - Isaacs, D
Abstract : Antibiotic use selects for antibiotic resistant bacteria. This is an example of rapid Darwinian natural selection in action. It occurs in neonatal intensive care units with the use of parenteral antibiotics, and in the community with oral antibiotic use. A 10 point plan is put forward to reduce antibiotic resistance in neonatal units.